Local Identities Landscape and Community in the Late Prehistoric Meuse-Demer-Scheldt Region - Gerritsen, Fokke (Amsterdam Archaeological Studies, 2003)
Investigates how small groups - households and local communities - constitute and represent their social identity by ordering the landscape in which they dwell. The author develops a new theoretical and empirical perspective that deals with many of the practices that create collective senses of identity and belonging. These include house building and habitation, structured deposition, cremation and burial, arable farming, and ritual practices. An explicitly diachronic approach charts processes of cultural and social change which have previously gone largely unnoticed, providing a stimulating basis for a more dynamic history of the late prehistoric inhabitants of the Meuse-Demer-Scheldt region.